Composite phase change material and preparation method thereof
By synthesizing polyol phase change agents with long carbon chain side chains in flexible PCM and doping them with paraffin, the problems of high rigidity and latent phase change heat in engineering applications are solved, and composite phase change materials with high phase change latent heat, good mechanical properties and low surface hardness are achieved, which are suitable for efficient applications of thermal management interface materials.
Patent Information
- Application Number
- CN202411758963.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
Existing flexible PCMs are limited by rigidity and high latent heat of phase change in engineering applications, making it difficult to meet the multiple performance requirements of thermal management interface materials.
Through the click reaction of double bond-containing polyol and long carbon chain thiol, a polyol phase change agent with long carbon chain side chains is synthesized, and a polyol system is combined with polyethylene glycol and non-crystalline polyols to react with isocyanate to synthesize phase change polyurethane elastomers, doped with paraffin with high phase change latent heat, reduce the phase transition temperature of the material, improve the tensile strength and elongation of break, and reduce the surface hardness.
Composite phase change materials with high phase change latent heat, good mechanical properties and low surface hardness are achieved, which are suitable for efficient applications of thermal management interface materials.
Smart Images

Figure CN119570452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to a composite phase change material and a preparation method thereof. Background Art
[0002] As one of the thermal management interface materials, the phase change material (PCM) with designable structure has the advantages of easy assembly, low power consumption and uniform temperature between batteries, and is widely used in the heat dissipation system of batteries and electronic components. In the actual application of PCM thermal management system, engineering characteristics such as close contact between PCM and components, assembly without damage and appropriate operating temperature must be considered. Therefore, the ideal PCM should have high phase change latent heat, high elasticity at room temperature, good mechanical strength, suitable phase change temperature and no risk of liquid leakage.
[0003] Polyethylene glycol (PEG) has high crystallinity, non-toxicity, suitable phase transition temperature and outstanding structural stability. The PEG-based polyurethane (PU) solid-solid phase change material (PUPCM) prepared from it has received a lot of attention and research. PEG as a phase change agent generally has a molecular weight of more than 1000 and a melting temperature T m When the PEG content is greater than 30°C, it is equivalent to the existence of rigid segments in the PU molecular chain at room temperature. The more PEG is used in PUPCM, the higher the phase change latent heat of PUPCM, the greater the corresponding rigidity, and the more restricted the engineering application.
[0004] The current preparation strategy of flexible PCPUM is mainly to physically blend PEG monomers or PEG copolymers with flexible PU to reduce the influence of PEG crystal rigidity on the flexibility of PU molecular segments, but the effect still does not meet the application requirements.
[0005] Based on this, the present application aims to provide a composite phase change material and a preparation method thereof to better solve the above technical problems. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a composite phase change material and a preparation method thereof, wherein a polyol phase change agent with a long carbon chain side chain is synthesized by a click reaction between a double-bond polyol and a long carbon chain thiol. The polyol structure in the molecular chain of the phase change agent promotes the crystallization of the molecular chain and increases the latent heat of phase change. The polyol system is formed by combining the polyol with polyethylene glycol and non-crystalline polyol and reacting with isocyanate to synthesize a phase change polyurethane elastomer, and the elastomer is doped with paraffin with high phase change latent heat. The phase change temperature of the material can be effectively reduced, the tensile strength and elongation at break can be significantly improved, and the surface hardness can be significantly reduced, so as to obtain a composite phase change material with high phase change latent heat, good mechanical properties and low surface hardness, so as to be better used as a thermal management interface material.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing a composite phase change material comprises the following steps:
[0009] S1. Add a long carbon chain thiol, a double bond-containing polyol and a photoinitiator into a reaction vessel, and react under 365 nm ultraviolet light and 75-85 ° C for 5-7 hours to obtain an alkyl-modified polyol;
[0010] S2. The non-polar phase change agent, alkyl-modified polyol, polyethylene glycol and non-crystalline polyol are stirred and mixed evenly with cyanate ester, and vacuumed at 75-85°C for 2-3 minutes, then a catalyst is added and stirred rapidly for 2-4 minutes, and then a chain extender is added and stirred for 1-2 minutes. Finally, vacuumed at 75-85°C for 3-4 minutes, poured into a polytetrafluoroethylene mold at 95-105°C, and then placed in an oven for curing for 11-13 hours to obtain a composite phase change material.
[0011] Furthermore, in step S1, the molar ratio of the long carbon chain thiol to the double bond-containing polyol is 1-1.1:1; and the added amount of the photoinitiator is 0.5-1.0 wt%.
[0012] Furthermore, in step S2, the amount of non-polar phase change agent added is 2-15wt%, the amount of alkyl modified polyol added is 3-20wt%, the amount of polyethylene glycol added is 10-50wt%, the amount of non-crystalline polyol added is 10-30wt%, the amount of cyanate added is 4-10wt%, the amount of catalyst added is 0.05%-0.15%, and the amount of chain extender added is 1-5wt%.
[0013] Furthermore, in step S2, the molar ratio of NCO to OH in the mixed components is 1.0-1.1.
[0014] Furthermore, in step S1, the long carbon chain mercaptan is any one of dodecanethiol, hexadecanethiol, octadecanethiol and eicosanethiol.
[0015] Furthermore, in step S1, the double bond-containing polyol is any one of kaempferol, 2-butene-1,4-diol, but-3-ene-1,2-diol, hept-6-ene-2,4-diol, 3-hexene-1,6-diol, 1,5-hexadiene-3,4-diol and 3-allyloxy-1,2-propanediol.
[0016] Furthermore, in step S2, the non-polar phase change agent is any one of paraffin, dodecane, tetradecane, hexadecane, octadecane and eicosane.
[0017] Furthermore, in step S2, the non-crystalline polyol is any one of polyethylene adipate glycol, polycarbonate diol, polypropylene glycol, polyoxypropylene triol and hydroxy-terminated polybutadiene-acrylonitrile.
[0018] Further, in step S2, the chain extender is any one of propylene glycol, diethanolamine, triethanolamine, 4,4'-methylenebis(2-ethyl)aniline, 1,4-butanediol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, hexanediol and diethyltoluenediamine;
[0019] Further, in step S2, the cyanate is any one of diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, isophorone diisocyanate, toluene diisocyanate and dicyclohexylmethane-4,4-diisocyanate;
[0020] The molecular weight of the polyethylene glycol is 1000-10000.
[0021] Based on the same inventive concept, the present application also provides a composite phase change material prepared using the above preparation method.
[0022] The beneficial effects of the present invention are as follows:
[0023] The composite phase change material provided by the present invention is synthesized by a click reaction of a polyol containing a double bond and a long carbon chain thiol to form a polyol phase change agent with a long carbon chain side chain. The polyol structure in the molecular chain of the phase change agent promotes the crystallization of the molecular chain and increases the latent heat of phase change. The polyol system is formed by combining the polyol with polyethylene glycol and non-crystalline polyol and reacting with isocyanate to synthesize a phase change polyurethane elastomer, and the elastomer is doped with paraffin with high latent heat of phase change. The phase transition temperature of the material can be effectively reduced, the tensile strength and elongation at break can be significantly improved, and the surface hardness can be significantly reduced, so as to obtain a composite phase change material with high latent heat of phase change, good mechanical properties and low surface hardness, so as to be better used as a thermal management interface material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a differential scanning calorimetry curve diagram (melting process) of octadecyl mercaptan and allyloxypropylene glycol modified octadecyl mercaptan, wherein ODT-octadecyl mercaptan, MODT-allyloxypropylene glycol modified octadecyl mercaptan;
[0025] Figure 2 is a differential scanning calorimetry curve diagram (crystallization process) of octadecyl mercaptan and allyloxypropylene glycol modified octadecyl mercaptan, wherein ODT-octadecyl mercaptan, MODT-allyloxypropylene glycol modified octadecyl mercaptan;
[0026] Figure 3These are hot stage photographs of the phase change materials prepared in Comparative Examples 2-4 after being placed at 80° C. for 2 hours, wherein a is Comparative Example 2, b is Comparative Example 3, c is Comparative Example 4, and d is Comparative Example 5;
[0027] Figure 4 These are hot stage photographs of the phase change materials prepared in Examples 2-4 after being placed at 80° C. for 2 hours, wherein A is Example 2, B is Example 3, C is Example 4, and D is Example 5;
[0028] Figure 5 This is a dimensional stability test diagram of the phase change material prepared in Example 3 after being placed at 80° C. for 2 hours;
[0029] Figure 6 This is a dimensional stability test diagram of the phase change material prepared in Example 6 after being placed at 80° C. for 2 hours;
[0030] Figure 7 This is a dimensional stability test diagram of the phase change material prepared in Comparative Example 5 after being placed at 80° C. for 2 hours;
[0031] Figure 8 It is the melting curve diagram of the phase change material prepared in Comparative Examples 2-4, wherein P10 is Comparative Example 2, P20 is Comparative Example 3, P30 is Comparative Example 4, and P40 is Comparative Example 5;
[0032] Fig. 9 It is a crystallization curve diagram of the phase change material prepared in Comparative Examples 2-4, wherein P10 is Comparative Example 2, P20 is Comparative Example 3, P30 is Comparative Example 4, and P40 is Comparative Example 5. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively by way of examples, and preferred embodiments of the present invention are given below. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. Any other implementation schemes obtained by modifying or equivalently replacing the technical scheme of the present invention without creative results are within the protection scope of the present invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for describing specific embodiments and are not intended to limit the present invention.
[0035] The numerical values disclosed in the embodiments of the present invention are approximate values, not definite values. When the error or experimental conditions permit, all values within the error range may be included without being limited to the specific numerical values disclosed in the embodiments of the present invention.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0037] Example 1
[0038] This embodiment provides a method for preparing a composite phase change material, comprising the following steps:
[0039] S1. According to the molar ratio of 3-allyloxy-1,2-propanediol to octadecyl mercaptan of 1.1:1, 3-allyloxy-1,2-propanediol, octadecyl mercaptan and Photoinitiator 1173 (photoinitiator) (0.5%) were added to a 250 mL three-necked flask, and reacted for 6 hours under 365 nm ultraviolet light and 80° C. to obtain a crude product A. Then, the cooled A was poured into a conical funnel, and the unreacted reactants and initiators were removed by washing with a methanol / water solution and n-hexane in a volume ratio of 5:1 for multiple times. The washed product was transferred to a vacuum oven at 120° C. and dried for 2 hours to obtain allyloxypropylene glycol-modified octadecyl mercaptan;
[0040] S2. According to the molar ratio of NCO to OH of 1.07-1.08 and the addition amount of paraffin of 5wt%, paraffin, allyloxypropylene glycol-modified octadecyl mercaptan, polyethylene glycol and polyoxypropylene triol are stirred and evenly mixed with isophorone diisocyanate in proportion, and vacuumized at 80°C for 2-3 minutes, then 0.8wt‰ Bi(Oct)3 is added and stirred rapidly for 3 minutes, and then the chain extender MOEA is added and stirred rapidly for 1-2 minutes. Finally, the above mixture is vacuumized at 80°C for 3-4 minutes, poured into a polytetrafluoroethylene mold at 100°C, and then placed in an oven at 100°C for curing for 12 hours to obtain a product composite phase change material, recorded as PA / PCPUe.
[0041] The preparation steps of Example 2-5 are the same as those of Example 1, except that the amounts of components added are different. The specific component contents in Example 2-5 are shown in the following table:
[0042]
[0043] Comparative Example 1
[0044] This comparative example provides a method for preparing a composite phase change material. The preparation process thereof is different from that of Example 1 only in that, in step S2, paraffin is not added. The phase change material prepared in this comparative example is recorded as PCPUe.
[0045] Comparative Examples 2-5
[0046] The difference between Comparative Example 2-4 and Example 1 is that step S1 is not performed, and the phase change material is directly prepared by the same step as step S2 in Example 1, that is, allyloxypropylene glycol-modified octadecyl mercaptan is not added, and paraffin is not added.
[0047] The difference between Comparative Example 5 and Example 1 is that step S1 is not performed, and the phase change material is directly prepared by the same step as step S2 in Example 1, that is, allyloxypropylene glycol-modified octadecyl mercaptan is not added, but paraffin is added.
[0048] The contents of the components added in Comparative Examples 2-5 are shown in the following table:
[0049]
[0050] See also Figure 1-Figure 2 , which are differential scanning calorimetry curves of octadecyl mercaptan and octadecyl mercaptan modified with allyloxypropylene glycol. It can be seen that the propoxypropylene glycol structure in the molecular chain of octadecyl mercaptan modified with allyloxypropylene glycol promotes the crystallization of the molecular chain and increases the latent heat of phase change.
[0051] See Table 1 below, which is a phase change property test table of octadecyl mercaptan and octadecyl mercaptan modified with allyloxypropylene glycol.
[0052] Table 1 Phase change properties test table of octadecyl mercaptan and allyloxypropylene glycol modified octadecyl mercaptan
[0053]
[0054]
[0055] Note: The maximum value of the latent heat of phase change ΔH m-max =ODTwt%×ΔH m ODTJ / g
[0056] It can be seen from Table 1 above that the phase change latent heat of the allyloxypropylene glycol-modified octadecyl mercaptan in the present application is significantly improved. It is combined with polyethylene glycol and a non-crystalline trihydroxy polyoxypropylene ether cross-linker to form a diol system to synthesize PUPCM, and doped with paraffin with high phase change latent heat. The phase change temperature of PCPUe can be effectively reduced, the tensile strength and elongation at break can be significantly improved, and the surface hardness can be significantly reduced, thereby obtaining a composite phase change material with high phase change latent heat, good mechanical properties and low surface hardness.
[0057] See Table 2 below, which is a table of phase change properties of the composite material PA / PCPUe prepared in Example 1 of the present application, the composite material PCPUe prepared in Comparative Example 1, and phase change paraffin.
[0058] Table 2 Phase change properties test table of PA / PCPUe, PCPUe and paraffin
[0059]
[0060] As shown in Table 2 above, the melting temperature and crystallization temperature of PA / PCPUe are lower than those of PCPUe and paraffin, which indicates that PA / PCPUe can undergo phase change at a lower temperature, that is, the composite phase change material prepared in the embodiment of the present application effectively reduces the phase transition temperature.
[0061] See Table 3 below, which is a performance test table of the phase change materials prepared in Example 1 and Comparative Example 1.
[0062] Table 3 Performance test table of PCPUe and PA / PCPUe
[0063]
[0064]
[0065] It can be seen that the composite phase change material prepared in Example 1 of the present application, by incorporating paraffin with high phase change latent heat, weak intermolecular force and low rigidity, while also using a diol phase change agent with an octadecyl side chain synthesized by the reaction of allyloxypropylene glycol and octadecyl mercaptan, the surface hardness of the composite phase change material in the present application is reduced by 16A, the tensile strength is increased by 27%, and the elongation at break is increased by 500%. It can be seen that the PA / PCPUe prepared in the examples of the present application has good comprehensive performance and has great potential for application in thermal management interface materials.
[0066] See Table 4 below, which is a table showing the mechanical properties of the phase change materials prepared in Comparative Examples 2-5 and Examples 2-5:
[0067]
[0068] As can be seen from the above table, it can be seen that after paraffin and PCPUe are blended, the surface hardness decreases, the tensile strength decreases, and the elongation at break first increases and then decreases. This may be due to the fact that when the amount of paraffin is small, it has good compatibility with the allyloxypropylene glycol-modified octadecyl mercaptan in PCPUe, which plays a plasticizing role. However, when the amount reaches 10wt%, the paraffin is partially freed and forms a phase separation with PCPUe, which damages the tensile properties of PCPUe. The test results of DSC are further verified. Although the blending of paraffin and PCPUe will cause the mechanical properties of PA / PCPUe to decrease to a certain extent, the surface hardness of the phase change material in Comparative Example 5 with the same amount of phase change agent is reduced by 16A, the tensile strength is increased by 26.7%, and the elongation at break is increased by 500%, which has more engineering application value.
[0069] See also Figure 3 and Figure 4As shown, the phase change materials prepared in Comparative Examples 2-5 and Examples 2-5 of the present application are photographed on a hot stage after being placed at 80° C. for 2 hours (the phase change temperature is higher than its phase change temperature T m shape changes in the environment), from Figure 3 and Figure 4 It can be clearly observed that the shape of PCPUe synthesized by polyethylene glycol and allyloxypropylene glycol-modified octadecyl mercaptan remains stable after exceeding its phase transition temperature Tm, and there is no leakage, indicating that polyethylene glycol and allyloxypropylene glycol-modified octadecyl mercaptan are both involved in the synthesis of PCPUe to form a solid-solid phase change material.
[0070] See also Figure 5-Figure 7 As shown, it is a dimensional stability test diagram of the phase change materials prepared in Examples 3 and 6 of the present application and Comparative Example 5 after being placed at 80°C for 2 hours. In Comparative Example 5, MODT is not added, and only the PCPUe with polyethylene glycol is added with 5wt% paraffin. At a high temperature of 80°C, a relatively obvious leakage phenomenon occurs, while the PCPUe containing allyloxypropylene glycol modified octadecyl mercaptan in Example 3 does not leak after adding 5wt% paraffin. The PCPUe containing allyloxypropylene glycol modified octadecyl mercaptan in Example 6 leaks slightly when adding 10wt% paraffin. The above results show that polar polyethylene glycol-based PCPUe is prone to macroscopic phase separation when blended with non-polar paraffin, while the PCPUe containing allyloxypropylene glycol modified octadecyl mercaptan can be similarly compatible with a certain amount of paraffin due to the effect of the long carbon chain alkyl of the side chain, without macroscopic phase separation, and maintains good dimensional stability.
[0071] See also Figure 8-Figure 9 As shown, they are melting and crystallization curves of the phase change materials prepared in Comparative Examples 2-4, respectively. It can be seen from the figure that its CPUe crystal phase is separated and there is a risk of leakage, which is consistent with its shape stability test results.
[0072] In summary, the composite phase change material provided by the present application is synthesized by a click reaction of a double-bond polyol and a long carbon chain thiol to form a polyol phase change agent with a long carbon chain side chain. The polyol structure in the molecular chain of the phase change agent promotes the crystallization of the molecular chain and increases the latent heat of phase change. It is combined with polyethylene glycol and non-crystalline polyol to form a polyol system and reacted with isocyanate to synthesize a phase change polyurethane elastomer, and doped with paraffin with high phase change latent heat. The phase transition temperature of the material can be effectively reduced, the tensile strength and elongation at break can be significantly improved, and the surface hardness can be significantly reduced, so as to obtain a composite phase change material with high phase change latent heat, good mechanical properties and low surface hardness, so as to be better used as a thermal management interface material.
[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a composite phase change material, characterized in that: The steps include: S1. Add a long carbon chain thiol, a double bond-containing polyol and a photoinitiator into a reaction vessel, and react under 365 nm ultraviolet light and 75-85 ° C for 5-7 hours to obtain an alkyl-modified polyol; S2. The non-polar phase change agent, alkyl-modified polyol, polyethylene glycol and non-crystalline polyol are stirred and mixed evenly with cyanate ester, and vacuumed at 75-85°C for 2-3 minutes, then a catalyst is added and stirred rapidly for 2-4 minutes, and then a chain extender is added and stirred for 1-2 minutes. Finally, vacuumed at 75-85°C for 3-4 minutes, poured into a polytetrafluoroethylene mold at 95-105°C, and then placed in an oven for curing for 11-13 hours to obtain a composite phase change material.
2. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S1, the molar ratio of the long carbon chain thiol to the double bond-containing polyol is 1-1.1:1; and the added amount of the photoinitiator is 0.5-1.0 wt%.
3. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S2, the addition amount of the non-polar phase change agent is 2-15wt%, the addition amount of the alkyl modified polyol is 3-20wt%, the addition amount of the polyethylene glycol is 10-50wt%, the addition amount of the non-crystalline polyol is 10-30wt%, the addition amount of the cyanate ester is 4-10wt%, the addition amount of the catalyst is 0.05%-0.15%, and the addition amount of the chain extender is 1-5wt%.
4. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S2, the molar ratio of NCO to OH in the mixed components is 1.0-1.
1.
5. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S1, the long carbon chain mercaptan is any one of dodecanethiol, hexadecanethiol, octadecanethiol and eicosanethiol.
6. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S1, the double bond-containing polyol is any one of kaempferol, 2-butene-1,4-diol, but-3-ene-1,2-diol, hept-6-ene-2,4-diol, 3-hexene-1,6-diol, 1,5-hexadiene-3,4-diol and 3-allyloxy-1,2-propanediol.
7. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S2, the non-polar phase change agent is any one of paraffin, dodecane, tetradecane, hexadecane, octadecane and eicosane.
8. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S2, the non-crystalline polyol is any one of polyethylene adipate glycol, polycarbonate diol, polypropylene glycol, polyoxypropylene triol and hydroxy-terminated polybutadiene-acrylonitrile.
9. The method for preparing a composite phase change material according to claim 1, characterized in that: In step S2, the chain extender is any one of propylene glycol, diethanolamine, triethanolamine, 4,4'-methylenebis(2-ethyl)aniline, 1,4-butanediol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, hexanediol and diethyltoluenediamine; The cyanate is any one of diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, isophorone diisocyanate, toluene diisocyanate and dicyclohexylmethane-4,4-diisocyanate; The molecular weight of the polyethylene glycol is 1000-10000.
10. A composite phase change material prepared by the preparation method according to any one of claims 1 to 9.